PLC training based on a 3D virtual maquette control: an educational experience in automation - Lima, José (2010)
A virtual automation laboratory is usually used as a stand-alone application aiming an educational experience of process simulation and control where students have no contact with hardware. A better way to let students practice in a real PLC (Programmable Logic Controller) achieving the automation class programming skills is to use a maquette. This paper describes a PC application, behaving as a Virtual Maquette that emulates a three-dimensional real world where an external PLC controls its behavior receiving feedback from the plant. The developed interface connects the PLC to the PC through the parallel port. The Virtual Maquette is composed by a car parking where user requests gate open order while PLC supervises gate open/close command, traffic lights and night lighting. Cars movements captivate student’s attention and increases motivation to learn. The Virtual Maquette supports different ways of control allowing several simultaneous student groups to work in different solutions.